(untitled) (Eurasian Medical Research Periodical, 2024)
Preeclampsia is a severe variant of gestosis that occurs after the 20th week of gestational age, is characterized by multiple organ disorders with predominant damage to the central nervous system, and precedes eclampsia. It is manifested by headaches, nausea, vomiting, visual impairment, hyperreflexia, lethargy, drowsiness or insomnia. It is diagnosed based on data from daily blood pressure monitoring, general urinalysis, coagulogram, transcranial Dopplerography. Infusion therapy, anticonvulsants, antihypertensive, anticoagulant, membrane stabilizing agents are used for treatment. If the appointments are ineffective, an emergency caesarean section is indicated.